RANCANG BANGUN JASA DESIGN INTERIOR BERBASIS WEB DENGAN METODE WATERFALL - Devid, Devid; Hutabri, Ellbert (Universitas Putera Batam, 2026)
The development of information technology has encouraged the transformation of interior design services from conventional methods to web-based digital platforms. Manual interior design service processes often cause several problems, such as limited access to design references, ineffective communication between clients and designers, and unstructured promotional media. This study aims to design and develop a web-based interior design service system by applying the Waterfall method to ensure a structured and systematic development process. The Waterfall method is implemented through several stages, including requirements analysis, system design, implementation, testing, and maintenance. The system is developed using web technologies and provides key features such as a design gallery, service package selection, online ordering, order status tracking, and administrative data management. System testing is conducted using the Black Box Testing method to verify that all functions operate as expected. The results indicate that the developed system improves the effectiveness of interior design services, facilitates users in selecting design references, and expands digital promotional media. Therefore, this system can serve as an effective and integrated solution for developing web-based interior design services